An image of nurses and nursing in Poland in the media and in the opinion of various social groups. Systematic review of scientific literature from the years 2010-2017 - Machul, Michał; Chrzan-Rodak, Agnieszka; Bieniak, Monika; Bąk, Jadwiga; Chałdaś-Majdańska, Justyna; Dobrowolska, Beata (Nursing in the 21st Century, 2018)
AN IMAGE OF NURSES AND NURSING IN POLAND IN THE MEDIA AND IN THE OPINION OF VARIOUS SOCIAL GROUPS. SYSTEMATIC REVIEW OF SCIENTIFIC LITERATURE FROM THE YEARS 2010-2017 Introduction. Nursing is a profession of public trust with a fairly high position in various rankings examining the prestige of professions. Aim. Analysis of published research results on the image of nurses and nursing in Poland in the media and in the opinion of various social groups. Material and methods. A systematic review of Polish scientific literature from the years 2010-2017 was undertaken. A multi-stage search process was carried out in accordance with the adopted inclusion criteria, and then articles identified and accepted were subjected to a qualitative analysis. Results. Searching the Google Scholar database by accepted key words resulted in 10,663 records. After analyzing the titles and abstracts of these papers, 19 articles were subjected to further analysis. As a result of searching journals included in the Arianta database according to established key words, 10 articles were identified, 8 of which were qualified for further analysis. After removing duplicates, 17 articles were approved for the final analysis. Qualitative analysis of the research results published in these papers allowed to distinguish the following categories: an image of nurses and nursing in various social groups, elements of nurses’ image in the media and society, actions aiming at improving the image of nurses and nursing in Poland, changes in the image of nurses and nursing in Poland over the years and the direction of these changes. Conclusions. The issue of an image of nurses and nursing in the media and in the society has been a frequent subject of research of nurses in Poland in the recent years. These studies concern primarily opinions on the image of nurses and nursing, factors which determine the image of nurses and nursing in Poland, constitutive elements of the image, the possibility of improving the image and people/ institutions responsible for it.